Effect of Steam Cooking on Quality Characteristics of Shelf Stable Chicken Pickle - Singh, Shubha; Goswami, Meena; Pathak, Vikas; Verma, Arun Kumar; V, Rajkumar (Journal of Meat Science, 2019)
The present study was carried out to evaluate the effect of stream cooking (without pressure) on quality characteristics of shelf stable  chicken pickle. Chicken pickle was prepared as per method, prescribed by Das et al. (2013) with slight modifications. An attempt was  made to improve the quality characteristics of chicken pickle by precooking of marinated meat by steam cooking without pressure for  10, 15 and 20 minutes separately. There was a significant difference (P
Keywords: Chicken pickle; Quality characteristics; Steam cooking; Shelf stable; Sensory evaluation